(untitled) (Scientific journal of the Fergana State University, 2024)
In the article, the authors describe the structure, functions and scope of the World Trade Organization (WTO), as well as emphasize the role and importance of the organization’s Secretariat in conducting the trade policy of this organization. It was emphasized that the specialists of the Republic of Uzbekistan should learn from the experience of experts working in the Secretariat of the organization